Influence of psychosocial factors, sleep disturbances and genetic factors on pain sensitivity and temporomandibular disorder - Fiamengui, Livia Maria Sales Pinto (2014)
The present study aimed to evaluate the influence of psychosocial factors depression and anxiety, sleep disturbances poor sleep and bruxism, and single nucleotide polymorphisms of COMT Val158Met (rs4680), IL-1(3954 (rs:1143634), IL6-174 (rs:1800795), IL10-592 (rs:1800872), MMP1-1607 (rs:1799750) and TNF-308 (rs:1800629) as contributors to pain sensitivity and Temporomandibular Disorders. The sample comprised 291 subjects of both genders, with ages ranging from 18 to 65. Psychosocial factors were assessed using Beck Depression Inventory and Beck Anxiety Inventory. Pittsburg Sleep Questionnaire Index Sleep was used to determine sleep quality. Sleep bruxism was diagnosed in accordance with validated clinical diagnostic criteria proposed by American Academy of Sleep Medicine. The saliva samples for the DNA analysis were collected with the Oragene DNA self-collection kit. The single nucleotide polymorphisms analysis was performed using PCR. An algometer was used to record the Pressure Pain Threshold (PPT) value for the TMJ, masseter muscle and anterior temporalis. Linear multiple regression was performed to evaluate the influence of the variables on the PPT. The level of significance was set at p<0.05. In order to evaluate the influence of the above mentioned variables as contributors to TMD, all subjects were examined according to the American Academy of Orofacial Pain Guidelines for assessment, diagnosis and management of TMD and divided into two groups: group 1 (n=143) subjects without TMD and group 2 (n=148) subjects with TMD myofascial pain. Pearson chi-square test followed by a stepwise multivariate logistic regression was used for statistical analysis. The level of significance was set at p<0.05. According to the first analysis, the PPT of TMJ was negatively influenced by SNPs of COMT Val158Met (p=0.013) and IL6- 174 (p=0.006). No genetic influence was found for PPT of masticatory muscles, which were significantly influenced by poor sleep (p=0.003) and sleep bruxism (p=0.000). After the second analysis, sleep bruxism (p=0.000), poor sleep (p=0.000) and anxiety (p=0.003) were found to be associated with TMD. No association between TMD and the genetic profiles evaluated was found. The results provide evidence that pain sensitivity of TMJ is related to decreased COMT activity, and increased IL-6 activity, while pain sensitivity of masticatory muscles is influenced by sleep disturbances. On the other hand, sleep disturbances and anxiety were pointed as contributing factors for TMD.